Biblioteczna herstoria – opowieść o pierwszej kobiecie w Bibliotece Sejmu Śląskiego (PDF 2,84 MB) (Książnica Śląska, 2025)
The text restores the memory of the first woman employed in theSilesian Sejm Library in Katowice, and then in the Silesian PublicLibrary from 1931 to 1939. The woman was, completely forgotten,Irena Klonowska-Strzodowa, an extraordinary figure, a muse ofpoets, and a social and independence activist who paid with her lifefor the hardships of work in 1945. Although she worked in the library for a relatively short time she co-created its history and is worthrecalling in the jubilee year. She was also involved in Upper Silesia’spublic life, especially during the uprisings and the plebiscite. Fromsmall press notes, a few archival documents and fractions of memories, attempts were made to reconstruct the biography of this first librarian of the Silesian Sejm Library.